Comparison of US Strain Elastography and Entero-MRI to Typify the Mesenteric and Bowel Wall Changes during Crohn's Disease: A Pilot Study. (30th October 2017) - Lo Re, Giuseppe; Picone, Dario; Vernuccio, Federica; Scopelliti, Laura; Di Piazza, Ambra; Tudisca, Chiara; Serraino, Salvatore; Privitera, Giambattista; Midiri, Federico; Salerno, Sergio; Midiri, Massimo; Bartolotta, Tommaso Vincenzo; et al.
Abstract : Purpose. To evaluate and compare the mesenteric and bowel wall changes during Crohn's disease (CD) on ultrasonography (US) Strain Elastography (SE) and Enterography Magnetic Resonance Imaging (E-MRI). Methods . From July 2014 to September 2016, 35 patients with ileocolonoscopy diagnosis of CD were prospectively examined with E-MRI and in the same time with US and SE. Results . A total of 41 affected bowel segments and 35 unaffected bowel segments in 35 patients were evaluated. US-SE color-scale coding showed a blue color pattern in the fibrotic mesentery and bowel wall in 15 patients and a green color pattern in the edematous ones in 20 patients. The signal of the bowel wall and mesenteric fat was iso/hypointense on T2-weighted sequence in the fibrotic pattern (23/35 and 12/35 patients) and hyperintense in the edematous pattern (12/35 and 23/35 patients). Mean ADC values were, respectively, 2, 58 ± 0, 33 × 10 −3 for the fibrotic mesentery and 2, 14 ± 0, 28 × 10 −3 for edematous one. There was a statistical correlation between US-SE color-scale and T2 signal intensity and between the US-SE color-scale and ADC maps. Conclusions . US-SE, ADC, and signal intensity on T2-weighted sequences on MR prove to be useful tools for the evaluation of CD pattern.